Tragedia griega y religión (Minerva, 2019)
The author of the paper considers that Tragedy and Religion in Greece can be studied with successful results if the information that religious phenomenology offers is taken into account. In six tragedies by Aeschylus, Sophocles and Euripides the previous factor is acknowledged and in these works possible examples of the following religious phenomena: piety, acts of gods, criticism, prayer, shrine and power, are described.